Bimetallic Cu-Bi catalysts for efficient electroreduction of CO2 to formate - Li, Le; Jin, Xuan; Yu, Xiaohan; Zhong, Miao (Frontiers in Chemistry, 2022)
Electrochemical CO2 reduction offers an effective means to store renewable electricity in value-added chemical feedstocks. Much effort has been made to develop catalysts that achieve high Faradaic efficiency toward Formate production, but the catalysts still need high overpotentials to drive the CO2–to–formate reduction, leading to low energy efficiency. Here we report physical vapor deposition to fabricate homogeneously alloyed, compositionally controlled Cu1-xBix bimetallic catalysts with excellent electrical conductivity over a large area. Operating electrochemical studies in Ar-saturated and CO2-saturated electrolytes identified that Cu–Bi catalysts notably suppress the competing H2 evolution reaction and thus enhance CO2–to–formate selectivity. We reported a formate Faradaic efficiency of >95% at an improved cathodic potential of ~ –0.72 V vs. RHE and a high formate cathodic energy efficiency of ~ 70%. The electrochemical reaction is stable over 24 hours at a current density of 200 mA cm-2. The work shows the advantages of bimetallic catalysts over monometals for enhanced reaction activity and selectivity.